Longitudinal Ceiling Temperature Profile in an Inclined Channel Induced by a Wall-Attached Fire - Xubo Huang; Yongfeng Zhang; Wei Wang; Zhenxiang Tao (Fire)
Channel fire poses a great threat to personnel safety and structural strength, in which the temperature profile is worthy of attention. In this paper, the longitudinal temperature profile of a ceiling jet induced by a wall-attached fire with different channel slopes was experimentally investigated using a 1:8 reduced-scale channel. The results show the following: (1) For channel fire with a horizontal ceiling, the influence of the burner aspect ratio and source-ceiling height on the temperature profile is monotonous in the cases considered in this work. With a larger burner aspect ratio and larger source-ceiling distance, more ambient air could be entrained; hence, the longitudinal temperature under the ceiling decays faster. (2) For channel fire with an inclined ceiling, when the burner aspect ratio and source-ceiling distance remain constant, the asymmetric entrainment induced by the flame under larger channel slope leads to more hot smoke being transported upstream. Consequently, the temperature profile is not symmetric, with higher temperatures upstream and lower temperatures downstream. (3) Combining the influence of the burner aspect ratios, source-ceiling distance, and burner aspect ratio, the characteristic length scale was modified. Based on this, a model describing the ceiling temperature profile was proposed and then verified with previous data.